(untitled) (Western European Journal of Medicine and Medical Science, 2026)
Endothelin-1 (ET-1), a potent vasoconstrictor peptide composed of 21 amino acids and primarily synthesized by vascular endothelial cells, is regarded as a key biological mediator in the pathogenesis of respiratory diseases. Recent studies indicate that ET-1 is actively involved not only in the regulation of vascular tone but also in inflammatory processes, oxidative stress, cell proliferation, and the development of fibrosis. Elevated levels of ET-1 have been detected in pathologies such as chronic obstructive pulmonary disease, bronchial asthma, pulmonary arterial hypertension, and acute respiratory distress syndrome. This increase has been proven to be directly correlated with disease severity, the degree of hypoxemia, and systemic inflammation markers. By interacting with interleukin-6, tumor necrosis factor-alpha, transforming growth factor-beta, and other cytokines, ET-1 activates the inflammatory cascade, intensifies structural changes in lung tissue, and induces vasoconstriction and remodeling in the pulmonary vessels. Furthermore, signaling pathways mediated through endothelin receptors (ETA and ETB) play a crucial role in pulmonary vascular hypertrophy and smooth muscle cell proliferation. Consequently, the endothelin system is considered a promising therapeutic target for the treatment of respiratory diseases. This article analyzes current scientific data on the biological properties, molecular mechanisms, and pathophysiological role of Endothelin-1 in major respiratory diseases and highlights its clinical significance